(untitled) (قضايا سياسية, 2025)
This study addresses the future of cyber power as one of the active elements in shaping the strategies of regional powers, focusing on Iran as a prominent model in this field. The cyber space has become a new arena for influence and conflict, used by countries to enhance their power, limit the influence of their adversaries, and achieve political and security gains without resorting to traditional power. This research highlights how Iran, in light of the multiple challenges it faces, is moving towards developing its cyber capabilities as a strategic tool to compensate for weaknesses in other areas and to build an unconventional deterrent that enhances its position in its regional environment. The research focuses on analyzing Iran's cyber motives, objectives, challenges it faces, as well as the potential scenarios for the future use of this power within the context of conflicts in the Middle East.